Closed Formulas for Some New Degree Based Topological Descriptors Using M-polynomial and Boron Triangular Nanotube - Shin, Dong Yun; Hussain, Sabir; Afzal, Farkhanda; Park, Choonkil; Afzal, Deeba; Farahani, Mohammad R. (Frontiers in Chemistry, 2021)
In this article, we provide new formulas to compute the reduced reciprocal randić index, Arithmetic geometric1 index, SK index, SK1 index, SK2 index, edge version of the first zagreb index, sum connectivity index, general sum connectivity index, and the forgotten index using the M-polynomial and finding these topological indices for a boron triangular nanotube. We also elaborate the results with graphical representations.